2019
DOI: 10.1016/j.neuint.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell IRF4 signaling protects neonatal brains from hypoxic ischemic encephalopathy

Abstract: Interferon regulatory factor 4 (IRF4), a transcription factor recognized as a key regulator of lymphoid and myeloid cell differentiation, has recently been recognized as a critical mediator of macrophage activation. Previously we have reported that IRF4 signaling is closely correlated with anti-inflammatory polarization of microglia in adult mice after stroke. However, IRF4's role in the inflammatory response in the immature brain is unknown. Using a model of neonatal hypoxic ischemic encephalopathy (HIE) we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“… 8 , 9 Moreover, more recent studies have demonstrated that IRF4 could affect neuroinflammation after ischemic stroke and may serve as a potential therapeutic target for ischemic brain injury. 10 , 11 Interestingly, it has been identified that IRF4 is positively regulated by KDM6B demethylase and thus mediates inflammatory response. 12 The involvement of IRF4 in the homeostasis of mature B cells and the progression of human non-small cell lung cancer have been illustrated in a prior study, and the mechanism was shown to be through the regulation of the expression and activity of Notch2.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Moreover, more recent studies have demonstrated that IRF4 could affect neuroinflammation after ischemic stroke and may serve as a potential therapeutic target for ischemic brain injury. 10 , 11 Interestingly, it has been identified that IRF4 is positively regulated by KDM6B demethylase and thus mediates inflammatory response. 12 The involvement of IRF4 in the homeostasis of mature B cells and the progression of human non-small cell lung cancer have been illustrated in a prior study, and the mechanism was shown to be through the regulation of the expression and activity of Notch2.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we did not test the effects of rh-CSF1 on female rat pups. There is increasing evidence suggests that HIE is a sexually dimorphic disease [74]. Future studies are warranted to validate the other neuroprotective functions and potential mechanisms as well as gender differences associated with CSF1 after HI.…”
Section: Discussionmentioning
confidence: 99%
“…The acute innate immune response is critical in regulating neonatal HIE injury. Due to gender differences in pro-and antiinflammatory response, male infants are more susceptible to HI insult and develop severer long-term cognitive deficits than females with comparable brain damage [74]. Microglial activation and accumulation were previously identified as pathological markers for HIE in human infants [75].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR‐301 associated with IRF1 was indicated being implicated in the neuronal innate immune response 15 . Additionally, further studies have illustrated IRF4 as a transcriptional factor correlated with the inflammatory response in the brain and suggested it as a target for the injury of neonatal ischaemic brain 16 …”
Section: Introductionmentioning
confidence: 99%